(untitled) (Fiep Bulletin - online, 2014)
The functional capacity in this study is defined by the ability to perform routine activities independently, with an extensive functionality, this physical autonomy to perform the functions of daily life, making independent individual in the physical, social and cultural context, contributes to improved quality of general life. Objective: Evaluate the effects of the practice of functional training in improving the overall quality of life of elderly. Method: The study was performed using the prospective method, controlled, in the January-November 2013 period. The study included 27 elderly aged 60 to 72 years, with 12 practitioners of Functional Training classes (patient group) and 15 individuals not engaged in physical activity (Control Group). The sample size was calculated for a power of 85% and type I error of 5%. Was admitted an average variation of 15% between the pre and post-tests, and the sample size computed in 27 participants. To calculate the functionality and overall quality of life, the table of Berg (EEB) was used, which assesses the dynamic and static balance of individuals and the risk of falls, and (WHOQOL-Bref), which is a questionnaire divided into four domains (physical was used psychological, personal relationships and environment.). Conclusion: Was identified in this study that functional training for the improvement and maintenance of overall quality of life of older people through increases in strength, endurance, flexibility and functional autonomy.